Vascular Rings in Adults: Outcome of Surgical Management - Saran, Nishant; Dearani, Joseph; Said, Sameh; Fatima, Benish; Schaff, Hartzell; Bower, Thomas; Pochettino, Alberto (The Annals of thoracic surgery, 2019)
Limited data exist on the management of vascular rings (VR) in adults. We reviewed our experience of surgical treatment of these patients. All adult patients with VR (n = 65) who underwent VR repair (mean age, 45 ± 16 years; 33 women [51%]) from January 1972 to January 2018 were retrospectively reviewed. Anatomic variants were right arch with aberrant left subclavian artery (SA) and Kommerell diverticulum (KD) in 22 (34%), left arch with aberrant right SA and KD in 20 (31%), double aortic arch in 12 (18%), right arch with mirror imaging and persistent ligamentum off KD in 7 (11%), and others in 4 (6%). Indications for operation included dysphagia in 43 (63%), respiratory symptoms in 28 (43%), aneurysmal KD in 12 (18%), and dissection/rupture in 7 (11%). KD was found in 51 patients (78%). The surgical approach included left thoracotomy in 50 (77%), right thoracotomy in 7 (11%), sternotomy in 5 (8%), and hybrid repair in 3 (5%). A 2-stage repair with carotid-SA transposition, followed by transthoracic KD excision, was done in 51% of aberrant SA (n = 23). There was 1 early death. Morbidity included recurrent laryngeal nerve injury in 5 (8%) and chylothorax in 3 (5%). Symptomatic improvement occurred in 97%. Survival was 96.1%, 85.0%, and 73.4% at 1, 5, and 10 years, respectively. Dysphagia recurred in 9 (14%), which included 7 (11%) with esophageal dysmotility. Repair of VR in adults can be performed safely. Dysphagia is the most common symptom and improves in most after repair. Excision of the KD and aberrant vessel is the preferred approach to prevent acute aortic events or recurrent symptoms. Early operation should be considered with esophageal compression to avoid late dysmotility.